The management of zakat in Penang : the effectiveness of zakat distribution system by Pusat Urus Zakat (PUZ) / Nur Shazana Sha’rani - Sha’rani, Nur Shazana (Academy of Contemporary Islamic Studies (ACIS), 2016)
Like the prayer, zakat also was described in the Quran in general and not in details. Besides, the Quran does not explain rates, nisab, the type of property subject to zakat or alms conditions but it can be clearly understood from the hadith of the Prophet S.A.W however in terms of distribution of zakat, the Quran states that zakat should be distributed to the eight recipients of zakat distribution. The issue attract many citizens. People often questioned about the surplus millions undistributed zakat funs to the recipients. The excess zakat increasing from year to year. Thus, nowadays arise few questions of the effectiveness of the zakat distributions. Among the questions that arises was about the amount collected and the amount that being distributed to the recipients. Asnaf or the recipients received the highest zakat money and the factors that influence the effectiveness of the management of zakat distribution in Pusat Urus Zakat (PUZ). Thus, this paper aims to discuss in detail the issues above and lastly this paper also proposed some approaches to solve these issues. The study was conducted at the Penang Zakat Management Centre from 2010 until 2015.